2019
DOI: 10.5539/jfr.v8n4p111
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Particle Size of Grape Seed Flour and Their Effects on the Characteristics of Cookies

Abstract: This study investigated the effect of particle size and chemical composition of grape seed flour (GSF) on the physical, chemical and sensory quality of cookies. Results indicate that the chemical composition of GSF varied significantly with particle sizes and smaller particle fraction had higher ash, fat, protein and extractible polyphenol contents but lower dietary fiber. Inclusion of 2.5-10% GSF in the cookie formula enhanced darkening, increased thickness and hardness, increased polyphenol and dietary fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The protein content of grape pomace was reported to be more than 8 g/100 g (Beres et al, 2019;Sousa et al, 2014;Teles et al, 2019;Tseng & Zhao, 2013), whereas some studies (Abdrabba & Hussein, 2015;Maman & Yu, 2019) revealed higher proteins content in grape seeds, depending on the variety. Some studies showed that the protein content of grape peels can vary from 5.3 to 12.7 g/100 g (Deng et al, 2011;Maurer et al, 2019;Mendes, Xavier, Evtuguin, & Lopes, 2013;Mironeasa et al, 2019c), as it is shown in Table 1.…”
Section: Grape Byproducts Chemical Compositionmentioning
confidence: 99%
“…The protein content of grape pomace was reported to be more than 8 g/100 g (Beres et al, 2019;Sousa et al, 2014;Teles et al, 2019;Tseng & Zhao, 2013), whereas some studies (Abdrabba & Hussein, 2015;Maman & Yu, 2019) revealed higher proteins content in grape seeds, depending on the variety. Some studies showed that the protein content of grape peels can vary from 5.3 to 12.7 g/100 g (Deng et al, 2011;Maurer et al, 2019;Mendes, Xavier, Evtuguin, & Lopes, 2013;Mironeasa et al, 2019c), as it is shown in Table 1.…”
Section: Grape Byproducts Chemical Compositionmentioning
confidence: 99%
“…As the level of grape seed flour substitution increased, the antioxidant activity of the cookies also increased [75]. Furthermore, inclusion of 2.5 and 5% grape seed flour in wheat cookies resulted in a linear increase in total phenolics compared to control wheat cookies [76]. In a study by Antonic et al, grape seed flour was used for the fortification of waffles in concentrations of 1, 3, 5 and 10%, where the highest phenolic and antioxidant profile was demonstrated by 10% inclusion of grape seed flour [77].…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, coffee enriched with grape seed powder has been of superior quality in terms of fiber. When the previous studies were examined, it was determined that the crude fiber content of the coffee bean and the grape seed varied between 2.30-24.70% and 32.21-83.01%, respectively and this situation was due to the raw material composition (Maman and Yu, 2019;Grzelczyk et al, 2022;Oprea et al, 2022). Vazquez-Sanchez et al ( 2018) reported that the change in the chemical composition of polysaccharides in coffee, depending on the roasting process, affects the fiber content.…”
Section: Compositional Properties Of Coffee Bean and Grape Seedmentioning
confidence: 99%